coping stratygy for female adolosence in sman 1 wanadadi tahu pelajaran 2018/2019 - utama, forletus panggah (STKIP Muhammadiyah Pringsewu, 2019)
Abstract : Coping strategies are ways that individuals use to solve problems, overcome changes that occur and threatening situations both cognitively and behavior. Young women are a phase where a woman undergoes a process from childhood to adulthood.This study aims to look at coping strategies forgirl adolsence in SMA 1 Wanadadi. This study included quantitative descriptive research with a sample of 200 female adolescent respondents.The results of this study indicate that the self-activity of girl adolsence has good coping in themselves, the planning aspects of girl adolsence have very good planning, the self-control of girl adolsence is still lacking, seeking social support for young women is very good and has ways to find solutions to problems , in the aspect of acceptance of young adolescents, they have not yet been able to accept the reality that will occur if a problem occurs, the religious aspects of the majority of girl adolsence are very good and can reduce the problems in their dir by surrendering to God and praying.The conclusion of this research is that girl adolsence in SMA 1 Wanadadi have a good coping strategy Keyword : Coping strategy